ADDITION OF HYDROFOIL TO SHIP RESISTANCE ANALYSIS ON HALASAN CLASS BASED ON VALIDATION TEST RESULT - Sutrisno Sutrisno; Wawan Kusdiana; Ayip Rivai Prabowo; Muhammad Askhuri (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
KRI Halasan - 630 is one of the Fast Missile warships with a length of 60 Meters which apart of fast patrol boat class which belongs to TNI-AL. Accordance with the main function not only as a fast missile boat but also as a patrol ship killer, this ship was made to have a high ability in “hit and run”. Since the beginning of the manufacture and after being inaugurated as KRI in 2014 this ship is able to reach speed until 27 knot in full load. As time goes on the same conditions the speed that this ship can achieve is 25 knot at maximum speed. This can be caused by increase in value from the resistance of the ship. One way to reduce the value of the resistance of the ship is to minimize the Wet Surface Area(WSA) from the ship. By adding hydrofoil technology will produce lift force which could lift apart of the hull ship from the water so that Wet Surface Area from the ship will reduce. From the calculation, to lift on the hull of KRI Halasan Class 20 cm in full load condition at 25 knot knows that dimension for fore foil with tapered straight type are wingspan 4,6 m, wingroot 1,33 m, wingtip 0,5 m, and swept angle 11°. And dimension for aft foil with rectangular straight type are wingspan 5,3 m, wingroot and wingtip 1,365 m, and swept angle 0°. The ship resistance with hydrofoil is 265,5 KN, while in the same condition and speed from the ship without hydrofoil the value of ship resistance is 267 KN. By adding hydrofoil technology could reduce the ship resistance 1,5 KN. This values could make 19,29 KW or 25,86 Hp in power saving.Keywords : Hydrofoil technology, Ship Resistance, Halasan Class